Link and match implementation enhancing graduate capability and employability in vocational education - Tika Sylviani Gusti; Yasdinul Huda; Mukhlidi Muskhir; M. Giatman (Global Econedu, 2026)
Objective: This study examined the effects of Link and Match implementation on graduate capability and graduate employability in vocational education. Methods: A quantitative explanatory survey was conducted involving 116 respondents selected through total sampling from SMK Muhammadiyah 2 Cileungsi, including school management, Grade XII students, graduates, and industry representatives. Data were collected using a validated five-point Likert questionnaire and analyzed using descriptive statistics, Pearson and Spearman correlation, and multiple linear regression. Results: Graduate capability showed the strongest relationship with employability (r = 0.636), while Link and Match implementation significantly influenced graduate capability and employability. Together, both predictors explained 49.7% of the variance in graduate employability (R² = 0.497, p < 0.001). Conclusions: Strengthening sustainable school–industry collaboration and competency-based learning is essential for improving graduate capability and enhancing employability in vocational education.